Plastitar and pyroplastics as emerging vectors of coastal pollution: Chemical identification from Panjang Island (Java Sea) and Palm Beach, Florida - Dwi Amanda Utami; Lars Reuning; Lorenz Schwark; Robert K. Nelson; Bryan D. James; Robert F. Swarthout; Diane Buhler; Eliete Zanardi-Lamardo; Christopher M. Reddy (Marine Pollution Bulletin, 2026)

High‐resolution coral oxygen and carbon isotope records reveal temperature and autotrophy dynamics in a Mediterranean climate change hotspot - Diego K. Kersting; Thomas C. Brachert; Juan P. D'Olivo; Cristina Linares; Lars Reuning; Joan Lluís Riera; Philipp Spreter; Ulrich Struck; Marina J. Vergotti; Jens Zinke (Limnology and Oceanography, 2025)
The Mediterranean Sea is warming at a rate exceeding the global average. Long‐term, high‐resolution data are essential for contextualizing changes within broader temporal scales, and coral skeletons provide valuable environmental archives, especially in data‐sparse regions or as supplements to existing records. While coral‐based reconstructions are well established in tropical settings, they remain limited in temperate areas. As the only reef‐building zooxanthellate coral in the Mediterranean, Cladocora caespitosa is particularly important for expanding coral‐based environmental archives in these understudied regions. Here, we present records of δ 18 O and δ 13 C in the skeletons of C. caespitosa from a global change sentinel site in NW Mediterranean. This study provides the most accurate temperature–δ 18 O calibration equations for C. caespitosa , including a traditional linear model and a novel exponential model that better accounts for the region's wide seasonal temperature range. Both calibrations rely on long‐term in situ water temperature data and a multi‐corallite composite approach to reduce non‐climatic variability. Seasonal trends in δ 13 C reveal, for the first time, variation in the coral's autotrophy–heterotrophy balance, while geochemical anomalies in the skeletons signal thermal stress effects on biomineralization. Our findings establish C. caespitosa skeletons as critical archives for reconstructing anthropogenic warming and its ecological effects in the Mediterranean.

High levels of microplastics and microrubber pollution in a remote, protected Mediterranean Cladocora caespitosa coral bed - Lars Reuning; Lars Hildebrandt; Diego K. Kersting; Daniel Pröfrock (Marine Pollution Bulletin, 2025)

The Rowley Shoals atolls: Remnants of a Miocene great barrier reef on the north-west Australian margin - Jackson C. McCaffrey; Stephen J. Gallagher; Malcolm W. Wallace; Tanita Averes; Stanislaus G. Fabian; Katja Lindhorst; Lars Reuning; Sebastian Krastel (Global and Planetary Change, 2025)

Equilibrium Mg and K isotope fractionation between carnallite and saturated brine: Calibrations and applications - Zhiguang Xia; Yongjie Lin; Dongdong Li; Lars Reuning; Zhongya Hu; Chuan Liu; Jun Mu; Weiqiang Li (Geochimica et Cosmochimica Acta, 2024)

The mineralogic and isotopic fingerprint of equatorial carbonates: Kepulauan Seribu, Indonesia - Dwi Amanda Utami; Lars Reuning; Maximillian Hallenberger; Sri Yudawati Cahyarini (International Journal of Earth Sciences, 2021)
Kepulauan Seribu is an isolated patch reef complex situated in the Java Sea (Indonesia) and is a typical example for a humid, equatorial carbonate system. We investigate the mineralogical and isotopic fingerprint of Panggang, one of the reef platforms of Kepulauan Seribu, to evaluate differences to other carbonate systems, using isotope in combination with XRD and SEM analysis. A characteristic property of shallow water (< 20 m) sediments from Kepulauan Seribu is their increased LMC content (~ 10%) derived from some genera of rotaliid foraminifers and bivalves. The relative abundance of these faunal elements in shallow waters might be related to at least temporary turbid conditions caused by sediment-laden river runoff. This influence is also evidenced by the presence of low amounts of siliciclastic minerals below the regional wave base. Kepulauan Seribu carbonates are characterized by very low δ 13 C and δ 18 O values. This is related to the isotopically depleted riverine input. The δ 13 C DIC in riverine water is reduced by the contribution of 12 C from riverside mangroves. Deep atmospheric convection and intensive rains contribute 18 O-depleted freshwater in the river catchments, finally reducing salinity in the Java Sea. The depleted δ 13 C signature in carbonates is further enhanced by the lack of green algae and inorganic carbonates and abundance of coral debris. Low δ 18 O values in carbonates are favored by the high water temperatures in the equatorial setting. Since equatorial carbonates in SE Asia, including the Java Sea, are typically influenced by high turbidity and/or river runoff, the observed distinctively low isotope values likely are characteristic for equatorial carbonate systems in the region.

Buried pockmarks on the Top Chalk surface of the Danish North Sea and their potential significance for interpreting palaeocirculation patterns - Samaneh Masoumi; Lars Reuning; Stefan Back; Alessandro Sandrin; Peter A. Kukla (International Journal of Earth Sciences, 2014)